Social Media Fashion Influencers and Gen Z: Unraveling Purchase Intentions Through an Extended Theory of Planned Behavior (TPB) in Indonesia - Setyanta, Budi; Dwi Septiyanti, Nisa; Setyawan, Didik; Zailani, Abdullah; Irfan Luthfi, Muhammad (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
This research examines the critical role of fashion influencers on social media in shaping Generation Z’s buying intentions in Indonesia. It uses an extended TPB framework to fill a notable gap in existing studies. The study gathered responses from 400 participants through Google Forms, utilizing a convenient online approach. The research utilized PLS-SEM to examine the paths among the various variables involved in the study. The findings reveal that while PBC may not be an essential construct for purchase intention, it plays a vital role in shaping attitudes that ultimately guide those intentions. Subjective norms and credibility are critical components that profoundly influence attitudes and the drive to purchase. This research improves the understanding of how social media influencers affect Gen Z’s buying decisions, offering valuable insights for marketers targeting this group online